Antisecretory Factor 16 (AF16): A Promising Avenue for the Treatment of Traumatic Brain Injury—An In Vitro Model Approach - Nicola Vahrmeijer; Jurgen Kriel; Bradley M. Harrington; Anton Du Preez van Staden; Adriaan Johannes Vlok; Lize Engelbrecht; Andre Du Toit; Ben Loos (Journal of Molecular Neuroscience, 2024)
Traumatic brain injury (TBI) is caused by an external mechanical force to the head, resulting in abnormal brain functioning and clinical manifestations. Antisecretory factor (AF16) is a potential therapeutic agent for TBI treatment due to its ability to inhibit fluid secretion and decrease inflammation, intracranial pressure, and interstitial fluid build-up, key hallmarks presented in TBI. Here, we investigated the effect of AF16 in an in vitro model of neuronal injury, as well as its impact on key components of the autophagy pathway and mitochondrial dynamics. N2A wt cells were treated with AF16, injured using a scratch assay, and analysed using confocal microscopy, correlative light and electron microscopy (CLEM), flow cytometry, and western blotting. Our results reveal that AF16 enhances autophagy activity, regulates mitochondrial dynamics, and provides protection as early as 6 h post-injury. Fluorescently labelled AF16 was observed to localise to lysosomes and the autophagy compartment, suggesting a role for autophagy and mitochondrial quality control in conferring AF16-associated neuronal protection. This study concludes that AF16 has potential as a therapeutic agent for TBI treatment through is regulation of autophagy and mitochondrial dynamics.

Curcumin Rescues a PINK1 Knock Down SH-SY5Y Cellular Model of Parkinson’s Disease from Mitochondrial Dysfunction and Cell Death - Celia van der Merwe; Hayley Christy van Dyk; Lize Engelbrecht; Francois Hendrikus van der Westhuizen; Craig Kinnear; Ben Loos; Soraya Bardien (Molecular Neurobiology, 2017)